The many dimensions of laboratories’ interdisciplinarity - Jensen, Pablo; Lutkouskaya, Katsiaryna (Scientometrics, 2014)
Interdisciplinarity is as trendy as it is difficult to define. Instead of trying to capture a multidimensional object with a single indicator, we propose six indicators, combining three different operationalizations of a discipline, two levels (article or laboratory) of integration of these disciplines and two measures of interdisciplinary diversity. This leads to a more meaningful characterization of the interdisciplinarity of laboratories’ publication practices. Thanks to a statistical analysis of these indicators on 600 CNRS laboratories, we suggest that, besides an average value of interdisciplinarity, different laboratories can be mainly distinguished by the “distance” between the disciplines in which they publish and by the scale at which interdisciplinary integration is achieved (article or laboratory).